An evaluation of a brief anger management programme for offenders managed in the community using cross-lagged panel models. Issue 2 (5th May 2015) - Trimble, Timothy James; Shevlin, Mark; Egan, Vincent; O'Hare, Geraldine; Rogers, Dave; Hannigan, Barbara
Abstract : Purpose: – The purpose of this paper is to evaluate the effectiveness of a brief, Cognitive Behaviour Therapy-based group intervention in anger management with male offenders. All participants were the subject of a stipulation to attend the programme under a probation order, and were at the time of the study being managed in the community. Design/methodology/approach: – Totally, 105 offenders attended the anger management programme, which was delivered by the Probation Board for Northern Ireland (PBNI), between 2008 and 2010 across a range of centres, representing most regions of the province. Prior to treatment, the offenders completed two measures: The State Trait Anger Expression Inventory (STAXI), and the Stages of Change Scales (SCS). Both these measures were also completed at the end of the programme of treatment. Findings: – It was found that the programme significantly reduced the expression of anger as well as state and trait anger among offenders referred to the programme as measured by the STAXI. Both the action and maintenance subscales of the SCS were significant predictors of improvement in anger expression. The action subscale was shown to be a valuable predictor of readiness for change amongst the offenders. Originality/value: – Assessing an offender's readiness to change may enhance selection for specific rehabilitation programs thus reducing drop-out rates leading to a more efficient use of resources. This study demonstrates that those participants who were found to be more ready for change, benefited most from the intervention programme.